2018
DOI: 10.1038/s41396-018-0176-z
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term in situ permafrost thaw effects on bacterial communities and potential aerobic respiration

Abstract: The decomposition of large stocks of soil organic carbon in thawing permafrost might depend on more than climate change-induced temperature increases: indirect effects of thawing via altered bacterial community structure (BCS) or rooting patterns are largely unexplored. We used a 10-year in situ permafrost thaw experiment and aerobic incubations to investigate alterations in BCS and potential respiration at different depths, and the extent to which they are related with each other and with root density. Active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
80
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(95 citation statements)
references
References 93 publications
12
80
0
Order By: Relevance
“…Thus the changed nutrients may explain the significant influence of thawing status on the community structure and assembly processes. The community structure change due to permafrost thawing has also been proposed to be due to the colonization of microorganisms in active layer (Monteux et al, 2018), which coincides with the increased bacterial richness observed here (Fig. 2a).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Thus the changed nutrients may explain the significant influence of thawing status on the community structure and assembly processes. The community structure change due to permafrost thawing has also been proposed to be due to the colonization of microorganisms in active layer (Monteux et al, 2018), which coincides with the increased bacterial richness observed here (Fig. 2a).…”
Section: Discussionsupporting
confidence: 86%
“…In contrast, permafrost thawing substantially activates a diverse range of oligotrophic and copiotrophic bacteria, and enriches carbohydrate transporter and metabolism-related genes (Schostag et al, 2019). This leads to an increased bacterial richness and converged community metabolic functions, and the soil carbon being dominated by aliphatic carbon resulted from microbial transformation (Deng et al, 2015;Mackelprang et al, 2011;Monteux et al, 2018;Schostag et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The relative abundance between the same order of active and total microbes was quite different, and several OTUs of active microbes exhibited low abundances in the DNA‐derived microbial communities, including Enterobacteriales and Clostridiales, which might dismiss the activity of active microbes. Furthermore, the shifts in the clusters of the active microbial communities were similar to previous shifts in the total microbial community structure under long‐term warming and changes in metagenome functional genes under short‐term warming (DeAngelis et al, ; Mackelprang et al, ; Monteux et al, ).…”
Section: Discussionsupporting
confidence: 80%
“…Studies on the grassland of the Great Plains of the United States and the Tibetan Plateau have indicated a declining trend or nonsignificant change in the capacity of decomposing recalcitrant carbon, which appeared to be associated with stabilizing the topsoil carbon stock of the whole ecosystem (Yue et al, ; Zhou et al, ). The change in the microbial community structure was the result of warming (DeAngelis et al, ; Monteux et al, ), which in turn affected the feedback on climate change (Bardgett et al, ; Zhou et al, ). Considering the temperature effect, RNA‐derived microbial communities could be applied to explain heat feedback by influencing the CO 2 ‐C release rate (De Vrieze et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation